PTU-137 'Nutrient Sensing in the Human Gut: Investigation of the Co-Localization Rate Between Casr, T1R1 and GPR43 Receptors with Satiety Peptides in the Human Antrum, Terminal Ileum and Ascending Colon.'. (4th June 2013) - Galanakis, V; Peiris, M; Blacksaw, A L
Abstract : Introduction: Increasing evidence from animal studies show that apical nutrient sensing receptors, expressed in gut enteroendocrine cells, play a key role in the release of satiety peptides {1, 2} . Early human studies indicate a similar expression pattern of these receptors and role in peptide release {3} . In this study the anatomical relationship between amino acid sensing (CaSR), carbohydrate sensing (T1R1), and short chain fatty acid sensing (GPR43) receptors and appetite regulating peptides GLP-1, PYY, 5-HT was investigated in the human gut. Methods: Healthy full thickness human gut sections were incubated with primary and fluorescent secondary antibodies and they were viewed under the fluoroscopic microscope to investigate co-localization of the CaSR, T1R1 and GPR43 with the GLP1, PYY and 5HT. Results: The co-localization rate between CaSR and PYY, GLP1 and 5HT was 0%, < 1% and 43% in the antrum, 20%, 12% and 82% in the ileum and 26%, 14% and 91% in the colon, respectively. Co-localization of T1R1 and GLP1 was observed only in the antrum and the colon. GPR43 was not expressed. Conclusion: CaSR is expressed at protein level and is colocalized with PYY, 5HT and GLP1 in the human antrum, terminal ileum and ascending colon. T1R1 expression at protein level is very limited in all the tested tissues. GPR43 expression was not observed. The results suggest that CaSR is linked to PYY, GLP1 and 5HT release in the human gut, with data being stronger for the 5HT release. Disclosure of Interest: None Declared References: Sternini, et al. 2008. Enteroendocrine cells: a site of 'taste' in gastro- intestinal chemosensing. Curr Opin Endocrinol Diabetes Obes 15(1): 73–78. Frenchet et al. 2000. The effects of intestinal infusion of long-chain fatty acids on food intake in humans. Gastroenterology 2000; 119: 943–8. Page et al. 2012. Peripheral neural targets in obesity. British Journal of Pharmacology, 1568-RC.R1.